Do rich parents enjoy children less? - Marco Le Moglie; Letizia Mencarini; Chiara Rapallini (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
We investigate the role of individual labor income as moderator of the parental subjective well-being trajectories around the first childbirth. By analyzing the German Socioeconomic Panel Survey data, we find that high-income parents enjoy their first child less than low-income ones. In a low fertility country such as Germany, income seems therefore to matter negatively for parental subjective well-being after childbirth, though with important differences by gender. Among mothers, there is a positive and significant anticipation effect (i.e. increased subjective well-being) from becoming a parent, and this is higher for lower-income women. Conversely, during the years after the childbearing event, middle and high income women present a significant negative variation with respect to pre-child subjective well-being set-point, but only starting from the second year after childbirth. Among men, the anticipation effect is not present, whereas in the years following the childbirth there is an immediate strong decline in subjective well-being for fathers in the higher income groups. We discuss these findings in terms of preferences among different groups of parents and the differential costs of children - the latter closely related to difficulties in reconciling work and family.
Keywords: 330; first child; subjective well-being; individual income; Germany